A PROSPECTIVE STUDY ON THE EFFICACY OF METFORMIN IN OBESE AND NON-OBESE PATIENTS WITH POLYCYSTIC OVARY SYNDROME - v, Saveetha; I, Soma sundaram; P, Shanmugasundaram (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: The aim of the study was to assess the efficacy of metformin on fasting blood glucose (FBG), postprandial blood glucose (PPBG), total cholesterol (T. chol), blood pressure (BP), weight and hence body mass index (BMI) in women with polycystic ovary syndrome (PCOS). Methods: In a prospective study, 90 women aged 18-45 were treated with metformin 500 mg twice daily for 1 year. women were grouped as obese and non-obese based on their BMI. The changes in measured parameters were analyzed statistically. Results: There was a reduction in weight, systolic BP (SBP), FBG, PPBG and T. chol (p=0.04, p=0.03, p=0.032, p=0.037, p=0.042 and p=0.047, respectively) in the obese group. There was no significant difference in diastolic BP in both the groups. Conclusion: Metformin treatment lowered weight and SBP and T. chol in women with PCOS. FBG and PPBG were also reduced in obese patients while Non-obese women did not benefit from metformin. Keywords: Polycystic ovary syndrome, Metformin, Obese, Non-obese.